Intra-industry adjustment to import competition: theory and application to the German clothing industry - Horst Raff; Joachim Wagner (Kiel Institute for the World Economy (IfW), 2009)
This paper uses an oligopoly model with heterogeneous firms to examine how an industry adjusts to rising import competition. The model predicts that in the short run the least efficient firms in the industry become inactive, surviving firms face a fall in output, mark-ups and profits, and the average productivity of survivors increases. These pro-competitive effects of import penetration on the domestic industry disappear in the long run. The predictions for the short run are confirmed in an empirical study of the German clothing industry.
Keywords: F12; F15; 330; International trade; firm heterogeneity; productivity; clothing industry; Bekleidungsindustrie; Internationaler Wettbewerb; Import; Wirtschaftliche Anpassung; Produktivität; Industrieller Strukturwandel; Theorie; Deutschland